ACUTE RESPIRATORY VIRAL INFECTIONS (ARVI): PREVALENCE, CLINICAL SYMPTOMS, AND PREVENTION MEASURES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article highlights the significance of Acute Respiratory Viral Infections (ARVI) in modern medicine, its transmission factors, and its impact on public health. ARVI is one of the most common infectious diseases today, notably characterized by its active spread during the cold season. The diversity of viruses, high infectivity, and short incubation period cause the rapid prevalence of the disease. Therefore, early diagnosis, adherence to prophylactic measures, and applying correct treatment methods play a crucial role in maintaining the general health of the population. The article scientifically discusses the course of ARVI, its clinical signs, and effective prevention recommendations.